The satire of Buddhist priests and wisdom over blind faith: transition of Japanese Buddhist medieval thought shown in the Ujishūimonogatari - Villamor Herrero, Efraín (Mirai. Estudios Japoneses, 2021)
The Japanese anthology known as Ujishūimonogatari (13 a.C) contains 197 tales of large diversity. This collection has stories transmitted orally and located principally in the ancient capital of Kyoto. However, it also possesses popular tales, histories from early India, and a huge number of legends. Among its many references to well-known Buddhist believes from Japanese Medieval ages, this work focuses on an exhaustive analysis of the tales what satirize the figure of few priests. As a result of this work, it has found as a common characteristic of these priests, ignorance, a lack of morals, and bad behavior based on taking advantage of his high social status. This paper shown the intention entailed in the edition of, at least, on these tales, where critical thinking is exposed in the final morals over blind faith.
Keywords: Ujishūimonogatari; Medieval Buddhism; priests; setsuwa; Japanese literature